Seafloor hydrothermal activity along mid-ocean ridge with strong melt supply: study from segment 27, southwest Indian ridge - Xihe Yue (Nature Portfolio, 2019)
Abstract Continuous tow investigations have shown that the present vent field inventory along fast to intermediate spreading ridges may be underestimated by at least 3–6 times, while the limited towed line investigations of venting sites along slow to ultra-slow spreading ridges make it impossible to determine their distribution. The Chinese Dayang cruise has conducted detailed towed line surveys of hydrothermal activity on segment 27 of the ultra-slow spreading southwest Indian ridge in 2015. The results have identified as many as 9 hydrothermal fields along 85-km-long segment, including one confirmed hydrothermal field, three inferred hydrothermal fields and five suspected fields. Hydrothermal activities are not only limited along-axis but also found approximately 10 km away from the axis. These vent fields are likely powered by a seismically identified axial magma chamber, including melt migration along normal faults to flank areas. The calculated hydrothermal activity frequency on segment 27 is approximately 3.6–8 times higher than that calculated from the Interridge database, suggesting that careful system exploration can reveal more hydrothermal activities even on ultra-slow spreading ridges effected by hotspot.